Examination Hall Centralized Mobile Detection System Using IoT - Nalawade, S. B.; Paikrao, Pratik Milind; Lalge, Ketan Ramdas; Mundhe, Vijay Shivanand (International Journal of Research in Interdisciplinary Studies, 2025)
This project proposes a technology to detect a cellphone that is being used by a restricted user in a restricted area, and also show the location of the user, to prevent the user from continuous use of the cellphone. the right number is checked. However, it is often busy and take time for an outsized number of scholars. Therefore, to avoid his problem, automated detection and identification of phones has been integrated. Currently there are mobile jammer to jam the whole network, but only to seek out cell phones of scholars who have been present within the exam hall there. It automatically detects the activity telephone within the e-hall and displays this information with the mobile detector on the remote computer (administrator) within the GUI until it detects the message, room number, location, etc. That is, it determines the precise place. Calculates the space between position (detected) and detector, identify increasing boundaries, and add new dimensions to rooms like remote computers, switch from one room to a different.